Nilai-Nilai Pancasila Terpatri dalam Bhinneka Tunggal Ika Demi Terwujudnya Moderasi Beragama di Indonesia - Yanti Vidarosa Naibaho; Fidelis Den; Megawati Naibaho (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
The enthusiasm to preserve the values of Pancasila becomes the soul and "spirit" that maintains the integrity of the Nation and Indonesia. Indonesia, which has various differences, remains united with the motto "Bhinneka Tunggal Ika". This motto is realized in real action based on an attitude of openness, solidarity and love for the integrity of the Unity State of the Republic of Indonesia (NKRI). This awareness was born from the belief that the noble values of Pancasila can unite the Republic of Indonesia with all its diversity. The aim of this research is to raise collective awareness of the reality of diversity being a legacy of the ancestors and founders of the Republic of Indonesia that is maintained and developed, not as a vice versa which threat for unity. To explore this theme, the researchers used the library research method. Through the data found, the researchers processes it systematically and critically. The diversity that exists on the archipelago is a "gift" from Allah, the creator of the universe. The plurality of ethnicities, religions, races and groups (SARA) is the uniqueness and beauty of Indonesia compared to other countries. An important implication to be promoted is respect for ethnic, cultural and religious differences as beautiful "flowers" in harmonious living together. In this way, every citizen tries to live up to the values of Pancasila. Pancasila is a modus vivendi that mobilizes groups of citizens to contribute to the construction of a "new home" in this country by uniting the vision, mission and sense of national solidarity.